Acceleration of cardiovascular-biological age by amphetamine exposure is a power function of chronological age. Issue 1 (9th February 2017) - Reece, Albert Stuart; Norman, Amanda; Hulse, Gary Kenneth
Abstract : Background: Amphetamine abuse is becoming more widespread internationally. The possibility that its many cardiovascular complications are associated with a prematurely aged cardiovascular system, and indeed biological organism systemically, has not been addressed. Methods: Radial arterial pulse tonometry was performed using the SphygmoCor system (Sydney). 55 amphetamine exposed patients were compared with 107 tobacco smokers, 483 non-smokers and 68 methadone patients (total=713 patients) from 2006 to 2011. A cardiovascular-biological age (VA) was determined. Results: The age of the patient groups was 30.03±0.51–40.45±1.15 years. This was controlled for with linear regression. The sex ratio was the same in all groups. 94% of amphetamine exposed patients had used amphetamine in the previous week. When the (log) VA was regressed against the chronological age (CA) and a substance-type group in both cross-sectional and longitudinal models, models quadratic in CA were superior to linear models (both p<0.02). When log VA/CA was regressed in a mixed effects model against time, body mass index, CA and drug type, the cubic model was superior to the linear model (p=0.001). Interactions between CA, (CA) 2 and (CA) 3 on the one hand and exposure type were significant from p=0.0120. The effects of amphetamine exposure persisted after adjustment for all known cardiovascular risk factors (p<0.0001). Conclusions: These results show that subacute exposure to amphetamines is associated with an advancement of cardiovascular-organismal age both over age and over time, and is robust to adjustment. That this is associated with power functions of age implies a feed-forward positively reinforcing exacerbation of the underlying ageing process.